Historical survey and emerging challenges of manufacturing automation modeling and control: A systems architecting perspective. (2019) - Morel, G.; Pereira, C.E.; Nof, S.Y.
Abstract: An architecting perspective is derived as part of a more global perspective, related to manufacturing automation modeling and control through four industrial revolutions. This historical survey (Pereira et al., 2017) highlights the impact of digitalization both on isolated machines and devices, and on the architecting of large-scale manufacturing and logistics systems. To distribute the holistic control over related components, two main paradigms have been followed for the engineering of those System of Systems (SoS): (1) technology-enhanced, and (2) bio-inspired. In both, the cognitive orchestration of the knowledge and skills involved in a system project remains challenging for the interdisciplinary togetherness and harmony required beyond the disciplinary boundaries. Finally, lessons learned, as well as acquired knowledge through this innovative history are addressed with several open questions and emerging challenges related to the cyber-physical systems evolution.